2006
DOI: 10.2355/isijinternational.46.161
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Evolution in a Low Carbon Nb–Ti Microalloyed Steel

Abstract: The micro mechanical properties, stability and three-dimensional (3D) morphology of intragranular ferrite was studied in a low carbon microalloyed steel utilizing nano indentation, three-dimensional reconstruction techniques along with LEO1 450 scanning electronic microscopy. The mixed microstructures of intragranular ferrite, granular bainite and lath or plate-like bainite was obtained in a Nb-Ti microalloyed steel, which was water cooled immediately after relaxation for a fixed time as hot deformation ended.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…[147], TiN particles served as nucleation sites for proeutectoid ferrite preferentially and also accelerated its formation in low-carbon alloy steels. TiN is regarded as an effective nucleation sites for intragranular ferrite owing to low interfacial energy between ferrite and TiN.…”
Section: Effect Of Ti Addiationmentioning
confidence: 98%
See 4 more Smart Citations
“…[147], TiN particles served as nucleation sites for proeutectoid ferrite preferentially and also accelerated its formation in low-carbon alloy steels. TiN is regarded as an effective nucleation sites for intragranular ferrite owing to low interfacial energy between ferrite and TiN.…”
Section: Effect Of Ti Addiationmentioning
confidence: 98%
“…In some studies it is suggested that, for titanium containing steel, the MnS is found to be precipitate on titanium oxides and stimulaing the nucleation of acicular ferrite [15].The formation of bainite or intragranular ferrite will found [131] dependend on the amount of sulphur added to the steel. So small concentration of sulphur (S ≈ 0.005 wt %) can sometimes stimulate the nucleation of bainite and resulting decrease in absorved energy [131,165].Moreover, the formation of intragranular ferrite plate IFP is promoted by increasing amount of sulfur (0.06-0.07 wt% S) due to increase the number of MnS particles as an effect off sulfur addition , resulting an increase in absorved energy (Fig.2.50-C), due to increase the resistance to the propagation of brittle fracture which is dominant in fracture mode at lower temperature, however as the amount of sulfur addition in large quantities, the MnS particles coarsened and acts as crack initiation points, there by promoting brittle fracture [46,131].Some researches indicate that the intragranular ferrite is caused by the formation of Mn depleted zone around inclusions [147].The precipitation of…”
Section: Effect Of Sulfur and Managanesementioning
confidence: 99%
See 3 more Smart Citations